Developing Students' Character through Physical Education in Primary Schools - Sinaga, Ayu Zahra (Jurnal Pendidikan, Kesehatan dan Olahraga, 2023)
Physical education is one of the solutions to instil character values in the primary school environment. Teachers must have a sense of responsibility to instil values and standards in students through the teaching process, both in teaching and learning activities and outside of teaching and learning activities such as reflection on good behaviour to the students themselves, which aims to be able to instil and change the character, especially the discipline character of students for the better. This research uses qualitative library research by collecting library materials from various writings, both books and journals, related to the implementation of character education in civic education, both in international and national journals. Therefore, dealing with the morality of character education of children from early age is the most important key to be built and implemented in the life of the state. Thus, the character of students who can personally follow school rules is the most needed character in the school environment, namely through physical education. The conclusion of this research shows that through physical education subjects is a way to shape the character of students. Therefore, character development in primary schools is the most important thing in creating moral and disciplined learners in the life of the country. Character development is also influenced by the conditions and environment in which students grow and develop. It is hoped that physical education that instills character values can have a positive impact on the moral and character development of students.